1993
DOI: 10.1159/000263839
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hemochromatosis: A Rare Cause of Nonimmune Hydrops fetalis and Fetal Anemia

Abstract: Neonatal hemochromatosis is a rare inherited disorder of iron metabolism in which various tissues contain excessive amounts of iron. Only in a very few cases in which the disease is associated with fetal nonimmune hydrops is there the possibility for prenatal diagnosis. We present a case of fetal nonimmune hydrops fetalis in which severe fetal anemia and elevated liver enzymes were found. Retrospectively, according to pathological examination, these were signs of neonatal hemochromatosis. Only the knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…The prenatal diagnosis may be raised, similarly as in our case, in front of hepatic abnormalities, especially fetal hepatomegaly and heterogeneous or multinodular liver architecture. Ascites or nonimmune hydrops fetalis, which are related to cirrhosis and anemia, may be detected on fetal imaging as shown in this report and in few previously published cases . Other nonspecific abnormalities are reported including intrauterine growth restriction and oligohydramnios, or polyhydramnios .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The prenatal diagnosis may be raised, similarly as in our case, in front of hepatic abnormalities, especially fetal hepatomegaly and heterogeneous or multinodular liver architecture. Ascites or nonimmune hydrops fetalis, which are related to cirrhosis and anemia, may be detected on fetal imaging as shown in this report and in few previously published cases . Other nonspecific abnormalities are reported including intrauterine growth restriction and oligohydramnios, or polyhydramnios .…”
Section: Discussionsupporting
confidence: 68%
“…Ascites or nonimmune hydrops fetalis, which are related to cirrhosis and anemia, may be detected on fetal imaging as shown in this report and in few previously published cases. [7][8][9] Other nonspecific abnormalities are reported including intrauterine growth restriction and oligohydramnios, or polyhydramnios. 10 Ultrasound detected oligohydramnios in our case, that resulted in Potter's facies.…”
Section: Discussionmentioning
confidence: 99%
“…Post mortem Brought to you by | NDSU Library Periodicals Authenticated Download Date | 5/24/15 10:54 PM PH presenting symptoms are nonspecific, and generally reflect multisystem failure [14], including hydrops, especially recurrent non-immune hydrops as several authors [1, 2, 10, 18,25,27,28] have reported. Post mortem Brought to you by | NDSU Library Periodicals Authenticated Download Date | 5/24/15 10:54 PM PH presenting symptoms are nonspecific, and generally reflect multisystem failure [14], including hydrops, especially recurrent non-immune hydrops as several authors [1, 2, 10, 18,25,27,28] have reported.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal hemochromatosis is a clinical syndrome in which severe fetal liver injury causes iron overload due to poor regulation of maternofetal iron fl ux. It has also been reported in fetal hydrops and stillbirths (Wisser et al 1993 ). This entity is discussed here because it typically presents clinically as ALF at birth or shortly afterwards.…”
Section: Gestational Alloimmune Liver Disease (Gald)mentioning
confidence: 81%